POTENSI, PENGEMASAN DAN MODEL SALURAN DISTRIBUSI PEMASARAN PAKET WISATA PEDESAAN DI DESA BATUBULAN KANGIN - Devi Somiari, Ni Kadek; Sudana, I Putu; Dewi, NGAS. (Jurnal IPTA (Industri Perjalanan Wisata); Vol 8 No 2 (2020): Jurnal IPTA (December 2020)DO - 10.24843/IPTA.2020.v08.i02.p14, 2020)
Rural tourism development is very important to do because it is in line with the trend of sustainable tourism and the needs of new tourists. Batubulan Kangin Village has tourism potentials to develop as a rural tourism destination through a rural package tour. Mapping the village potential is very important to do to form a tour package. Marketing distribution channels need to be designed to reach the tourists as the consumer. The data were collected through observation, interviews, literature studies, and documentation. The informants were determined by purposive sampling and used descriptive qualitative technique to analysed the data. The result of this research shows that the natural attraction of Batubulan Kangin Village is rice fields scenery. The cultural attraction consists of authentic Balinese Cooking Class, offerings making class, and the village’s structure. Artificial attractions consist of a rice skin peeling process, wood carving gallery, Balinese Dance Studio, elementary school, Jaje Sirat House Production, Dug-Dug Mong Statue, and Balinese house. The amenities consist of food and beverage provision by Tumang Cooking Class. The accessibility is very adequate, and the ancillary service is potentially provided by the local communities. That potential can be packaged into a Half-day Cultural Cycling Tour Around Batuyang Village and 3 Days 2 Nights Tour Exploring the Authentic Way of Batuyang Village’s Life. The tour packages are managed and marketed directly via the internet, as well as collaborating with tourism drivers, tour guides, Five Pillar Experiences, GODEVI, and market places as the indirect marketing distribution channel.